ANALISIS PERBANDINGAN JIWA KEWIRAUSAHAAN MAHASISWA JURUSAN AKUNTANSI SYARIAH DAN EKONOMI SYARIAH - Amkhana Desyafitri; Muhammad Qoes Atieq (Universitas Ahmad Dahlan, 2020)
Students in the millennial era now have many who run the business. Entrepreneurial spirit slowly grows in students. Not infrequently, many students study while doing entrepreneurship. The entrepreneurial spirit in this study refers to the explanation (Meredith, 1992 ) of the region. The entrepreneurial spirit that is owned by oneself consists of self-confidence, task-oriented, and outcome, dare to take risks, have leadership spirit, originality (authenticity) of business, and oriented into the future. The purpose of this study is to find out and explain the comparison of the Entrepreneurial Spirit in the department of sharia accounting and sharia economics. This type of research is a comparative descriptive study with a quantitative approach. Retrieving data using online questionnaires distributed to students majoring in accounting and economics sharia IAIN Sheikh Nurjati Cirebon. A sample is used as much as 186 people from the respondents accounting majors sharia as much as 93 and majoring in Islamic economics as much as 93. Whereas the data analysis uses descriptive analysis, inferential analysis, and one way ANOVA to compare. The results showed that there was no difference between the spirit of entrepreneurship in the department of sharia accounting and sharia economics.